Breast examination as a cost-effective screening tool in a clinical practice setting in Ibadan, Nigeria. (2013)
Background: Breast cancer is a disease of public health importance. It results in high morbidity and mortality in women worldwide. The high morbidity and mortality from breast cancer can be decreased by measures targeted at early detection such as screening. Breast examination as a screening tool for breast cancer in developing countries is advocated in view of its cost-effectiveness. Method: The article selection method was obtained from primary and secondary literature sources which included original research articles, case control studies, review articles, proceedings, transactions and textbooks. The authors cited a clinical audit and articles published between 1988 and 2011. The search strategy included the use of internet search engines. This review was part of a larger research and the study protocol was approved by University of Ibadan/University College Hospital, Ibadan Institutional Review Board (UI/UCH-IRB). Clinical trial registration number: NHREC/05/01/2008a. Results: Breast self-examination (BSE) and clinical breast examination (CBE) as screening tools for breast cancer were analysed in detail. Conclusion: Breast examination is a screening tool that is cost-effective and reliable and should be encouraged in resource-constrained countries. Given the high cost and expertise required for mammography, current efforts at screening for breast cancer in developing countries should rely more on a combination of BSE and CBE